ChemInform Abstract: Metal‐Free Reductive Cleavage of C—N and S—N Bonds by Photoactivated Electron Transfer from a Neutral Organic Donor. Issue 30 (29th July 2014) - O'Sullivan, Steven; Doni, Eswararao; Tuttle, Tell; Murphy, John A.
Abstract A recently reported neutral donor is used as efficient reagent for metal‐free reductive cleavage of different types of amino‐substrates under photolytic radical conditions.